Morphological differentiation in Asian honey bee (Apis cerana) populations in the basin and highlands of southwestern China. Issue 3 (27th May 2017) - Zhu, Xiangjie; Zhou, Shujing; Xu, Xinjian; Wang, Jianwen; Yu, Yinglong; Yang, Kai-chieh; Luo, Qun; Xu, Yingying; Wang, Shunhai; Zhou, Bingfeng
Abstract : In the evolutionary process, honey bee populations became divergent due to geographical barriers or ecological adaptation, but to date which specific barriers and ecological isolation conditions that blocked the honey bee gene flow remain uncertain. Here, the morphometric divergence of Apis cerana was studied across southwestern China, a region of diverse topography, featuring a low-elevation basin in the east and a high-elevation mountain and plateau in the west. A multivariate morphometric analysis was conducted on 1482 A. cerana individuals from 25 sampling sites across Sichuan province. The populations dwelling in high-elevation areas with larger body sizes and darker coloration were differentiated from the eastern low-elevation basin population. Moreover, the populations dwelling in the Jinshajiang, Yalongjiang, and DaduRiver Valleys showed significant divergence. Our data indicate that the morphometric variation between the high and low altitudes, probably due to the adaptation to the integrated effects of ecological factors such as air temperature, humidity, the nectar and pollen plants, and light intensity etc. Additionally, the mountains with an altitude of more than 3300 m and a honey bee-free zone probably served as a barrier to gene flow between the river valley populations.